Structure-evolving bioadhesive for temporally programmed osteoimmune modulation in osteoporotic bone regeneration - Qingda Li; Yurong Chen; Yining Gong; Yuan He; Bin Zhu; Senyu Xue; Luyao Feng; Yiming Ren; Xiaoyu Wu; Lu Dang; Bo Zhang; Dali He; et al. (Chemical Engineering Journal, 2026)

Microenvironment-responsive phosphorescence carbon dots for infection visualization and wound regeneration - Meng Xue; Jiahui Tan; Zhiheng Li; Jiayi Chen; Lingling Qiu; Bing Qi; Yunyun Zhang; Yurong Wei; Xuewen He; Jie Wang (Analytica Chimica Acta, 2026)

Dual-catalytic effects of CoN4 sites: Suppressing shuttle effect and boosting four-electron transfer in ZnI2 batteries - Le Yang; Yurong You; Weihang Feng; Jingyuan Qiao; Ye Chen; Chengdong Zhao; Wei He; Xuelian Wu; ZhengMing Sun (Chemical Engineering Journal, 2026)

Genomic landscape of idiopathic male infertility and the pregnancy outcomes following assisted reproductive technology - Chen Tan; Tongyao Hu; Lanlan Meng; King Kin Lam; Qing Zhang; Xilin Xu; Shimin Yuan; Yurong Wang; Zilan Huang; Keren Zhou; Yong Li; Chunbo Xie; et al. (Science Bulletin, 2026)

Multiscale pulsating intensification and wavelet entropy-driven AI optimization of fluidized biomass hydrogen production - Runzhe Gao; Tianyu Wang; Yurong He; Yifei Hu; Yufeng Zeng (Chemical Engineering Journal, 2026)

Oxygen-driven restructuring of Fe5C2 inhibits the Iron-based catalyst CC coupling in CO2 hydrogenation - Baojian Chen; Lingyu Jia; Fugui He; Bingbing Liao; Shanshan Dang; Weifeng Tu; Yurong He; Noritatsu Tsubaki; Zhenzhou Zhang; Yi-Fan Han (Chemical Engineering Journal, 2026)

Organic fertilization alleviates soil sickness in monoculture systems by driving pathogen-suppressive rhizosphere community assembly - Tong Peng; Chuanji Zhang; Xiaoqi He; Zhenyu Cheng; Junjie Li; Yanfang Song; Ziyu Liu; Meiyun Pu; Yi Yan; Panshuai Fei; Yurong Bi; Xiaofan Na (Plant and Soil, 2026)

Remediation of cadmium-contaminated soils by mercaptosuccinic acid-intercalated hydrotalcite: Effects on soil quality and cadmium accumulation in rice - Liqin He; Changfeng Ding; Min Nie; Ting Li; Ziyao Li; Taolin Zhang; Yurong Wang; Xingxiang Wang (Journal of Environmental Management, 2026)

Effects of grassland enclosure on phosphorus bioavailability and microbial nutrient limitations in the karst region of southwest China - Wangjun Li; Xiaolong Bai; Shun Zou; Bin He; Yurong Yang (European Journal of Soil Biology, 2026)

Moderate irrigation quotas enhance cotton growth in slightly saline soils by stabilizing the rhizosphere microbiome - Yurong Chang; Mingsi Li; Yulong Zhao; Dongwei Li; Shuai He (Irrigation Science, 2026)

Green photocatalytic conversion of CO2 to renewable fuel over Ag/Cu-TiO2/g-PAN nanofibers under solar irradiation - Shanshan Sun; Yurong He; Tianqi Tang; Siyu Hui (Journal of Cleaner Production, 2026)

Exposure to titanium and nickel as the novel risk factors for PCOS: Evidence from a case control study in Xiamen, China - Zhineng Fu; Lanlan Liu; Jingyi Wang; Fengkai Ruan; Yurong Chen; Liying Zhou; Chunyan Yang; Jiali Cai; Runzeng Liu; Chengyong He; Xiaoming Jiang; Zhenghong Zuo (Journal of Environmental Sciences, 2026)

Comparison of indigenous and exogenous microbiota: necessity of inoculation for lactic acid production - Yuan Li; Yueji Chen; Zonghai Du; Jinling He; Yurong Zhang; Yonghong Ma; Shuanglan Cheng; Xianbao Xu; Wenjuan Zhang; Ai Zhang; Xiang Li; Xu Duan; et al. (Bioresource Technology, 2026)

Distinguishing the impact of river discharge and submarine groundwater discharge on phytoplankton community in coastal water - Wenzhao Liang; Xin Luo; Meiqing Lu; Yurong Song; Yi Liu; Zhao Liang Chen; Ding He; Jiu Jimmy Jiao (Water Research, 2025)

Developed DNS-DEM coupling model for normal collisions of ellipsoidal particles on wet surfaces - Zhichao Song; Yurong He; Jingda Xia; Tianqi Tang (Chemical Engineering Journal, 2025)

Comparison of Lycium barbarum and Chenopodium glaucum litter decomposition reveals differential impacts on fusarium abundance and microbial community structure under field conditions - Chuanji Zhang; Zhenyu Cheng; Xiaoqi He; Meiyun Pu; Junjie Li; Ziyu Liu; Xiaomin Wang; Yurong Bi; Liguang Wang; Xiaofan Na (Applied Soil Ecology, 2025)

Soil aggregates stability is evidently enhanced by super-binding of the N-terminal disordered tail of glomalin to soil minerals - Minghui Jia; Youchao Wang; Jin He; Shan-Ho Chou; Dehua Luo; Linchuan Fang; Jingtao Hou; Yuke Fan; Wenjun Zhang; Hansong Chen; Dejian Zhou; Yurong Liu; et al. (Soil Biology and Biochemistry, 2025)

Assessing cumulative impacts of cascade dams on vegetation in the Reservoir–Hydropower impact zone - Yuanyuan Wang; Xiaolong He; Yurong Wang; Kefeng Li (Journal of Environmental Management, 2025)

Gas-solid dual barrier strategy to efficiently enhance flame-retardancy and smoke-suppression of cellulose aerogel - Xiaolei Luo; Linyue He; Longfei Sun; Xinxin Chen; Lin Liu; Juming Yao; Yurong Cai (Carbohydrate Polymers, 2025)

Study on coal-based solid state reduction of Panzhihua ilmenite - Wu Pengsen; He Benliu; Chen Jianli; Zhang Yurong; Du Jingwei; Muhammad Moeen; Gong Junju; Guo Yufeng; Qiu Guanzhou (Minerals Engineering, 2025)

Enhanced cadmium removal from wastewater using ZnO/MgO coated organo-mineral composites of biochar and bentonite: A comparative adsorption study - Saqib Bashir; Yurong Wang; Ziyao Li; Liqin He; Muhammad Adnan; Xingxiang Wang (Journal of Water Process Engineering, 2025)

Dual-signal amplified aptasensor based on PtPdAu mesoporous nanozymes with DNA walker-CHA for ultrasensitive DON detection - Jia Wu; Baoshan He; Gengan Du; Yurong Zhang; Chunqi Bai; Longdi Wang (Analytica Chimica Acta, 2025)

The double-edged sword effect of sulfate: enhanced stress tolerance but increased arsenic accumulation in rice grains - Yuepeng YIN; Min NIE; Yurong WANG; Liqin HE; Xin TANG; Zhigao ZHOU; Taolin ZHANG; Xingxiang WANG (Pedosphere, 2025)

UV-B stress reshapes root-associated microbial communities and networks, driven by host plant resistance - Chuanji Zhang; Na Gao; Xiaofan Na; Kaile Li; Meiyun Pu; Hao Sun; Yanfang Song; Tong Peng; Panshuai Fei; Junjie Li; Zhenyu Cheng; Xiaoqi He; et al. (Soil Biology and Biochemistry, 2025)

Evolution of interfacial electro-chemo-mechanics in high-energy-density NCM811||Si/C-composite Lithium-ion pouch cells - He Ma; Shujun Cai; Ran Song; Kexuan Jing; Min Wu; Weizong Wang; Yurong Ren; Qian Zhao; Zhengping Ding (Chemical Engineering Journal, 2025)

Acidic stability and mechanisms of soil cadmium immobilization by layered double hydroxides intercalated with mercaptosuccinic acid - Liqin He; Xingxiang Wang; Yuepeng Yin; Changfeng Ding; Gaoxiang Huang; Ziyao Li; Taolin Zhang; Yurong Wang (Environmental Research, 2025)

Mechanistic insight into accelerating of light olefin products by surface OH* group on the Fe5C2 catalyst - Fugui He; Xiangbin Kong; Tong Zhang; Shuai Zhang; Xinhua Gao; Kuan Lu; Yurong He; Jianli Zhang; Tiansheng Zhao (Fuel, 2025)

Reducing cadmium and arsenic accumulation in rice grains: The coupled effect of sulfur's biomass dilution and soil immobilization analyzed using meta-analysis and machine learning - Yuepeng Yin; Changfeng Ding; Xin Tang; Zhigao Zhou; Min Nie; Yuan Yuan; Yifan Qian; Liqin He; Ziyao Li; Zhihong Guo; Lirong Li; Qing Zhao; et al. (Science of The Total Environment, 2024)

A cost-saving, safe, and highly efficient natural mediator for laccase application on aflatoxin detoxification - Shenglong Liu; Yu Zhou; Yan Feng; Qixia Peng; Yurong Li; Cheng He; Zemin Fang; Yazhong Xiao; Wei Fang (Food Chemistry, 2024)

Corrigendum to “Selective and efficient immobilization of cadmium in soil by layered double hydroxides intercalated with the mercaptosuccinic acid” [Sci. Total Environ. volume 937, 10 August 2024, 173473] - Liqin He; Yurong Wang; Changfeng Ding; Gaoxiang Huang; Xiangming Tu; Zhigao Zhou; Yuepeng Yin; Xin Tang; Zhihong Guo; Ziyao Li; Taolin Zhang; Xingxiang Wang; et al. (Science of The Total Environment, 2024)

Unrevealing the coupling coordination degree between atmospheric CO2 concentration and human activities from geospatial and temporal perspectives - Yurong Zheng; Jianfei Wu; Shouhang Du; Wenbin Sun; Liming He (Science of The Total Environment, 2024)

The monokaryotic filamentous fungus Ustilago sp. HFJ311 promotes plant growth and reduces Cd accumulation by enhancing Fe transportation and auxin biosynthesis - Shengwang Wang; Xiaofan Na; Meiyun Pu; Yanfang Song; Junjie Li; Kaile Li; Zhenyu Cheng; Xiaoqi He; Chuanji Zhang; Cuifang Liang; Xiaomin Wang; Yurong Bi (Journal of Hazardous Materials, 2024)

Wolbachia titers are relate to sex determination of Trichogramma pretiosum - Zhuangting Xiao; Xin Xu; Qiling Liang; Congying Zhu; Xinyu He; Ruiling Hu; Yurong He; Desen Wang (Journal of Pest Science, 2024)

Electroacupuncture Alleviates Streptozotocin-Induced Diabetic Neuropathic Pain via the TRPV1-Mediated CaMKII/CREB Pathway in Rats - Yinmu Zheng; Siyi Li; Yurong Kang; Qunqi Hu; Yu Zheng; Xiaoxiang Wang; Hengyu Chi; Keying Guo; Minjian Jiang; Zhouyuan Wei; Xiaomei Shao; Chi Xu; et al. (Journal of Molecular Neuroscience, 2024)

Selective and efficient immobilization of cadmium in soil by layered double hydroxides intercalated with the mercaptosuccinic acid - Liqin He; Yurong Wang; Changfeng Ding; Gaoxiang Huang; Xiangming Tu; Zhigao Zhou; Yuepeng Yin; Xin Tang; Zhihong Guo; Ziyao Li; Taolin Zhang; Xingxiang Wang; et al. (Science of The Total Environment, 2024)

Oxygen incorporation facilitated MoS2 as an efficient and stable catalyst for the reverse water gas shift reaction - Yongning Yuan; Dongdong Zhai; Jianli Zhang; Jingjing Ma; Tuo Guo; Yurong He; Qingjie Guo (Chemical Engineering Journal, 2024)

Methods for quantification of biochar in soils: A critical review - Yanhai Xie; Caibin Li; Hanbo Chen; Yurong Gao; Tony Vancov; Brad Keen; Lukas Van Zwieten; Yunying Fang; Xiwen Sun; Yi He; Xiaofei Li; Nanthi Bolan; et al. (CATENA, 2024)

Monitoring of chlorophyll content in local saltwort species Suaeda salsa under water and salt stress based on the PROSAIL-D model in coastal wetland - Sen Zhang; Jia Tian; Xia Lu; Qingjiu Tian; Shuang He; Yali Lin; Shan Li; Wei Zheng; Tao Wen; Xinyuan Mu; Jun Zhang; Yurong Li (Remote Sensing of Environment, 2024)

Split activator of CRISPR/Cas12a for direct and sensitive detection of microRNA - Wen He; Xinyu Li; Xinmin Li; Minghui Guo; Mengxuan Zhang; Ruiwei Hu; Menghan Li; Shijia Ding; Yurong Yan (Analytica Chimica Acta, 2024)

Fabrication of hyaluronic acid-altered gold complex delivery for head and neck squamous cell carcinoma therapy with high antitumor efficacy and low in vivo toxicity - Shizhi He; Jiaming Chen; Yanming Zhao; Ru Wang; Yurong He; Shaoshi Chen; Yifan Yang; Changyu Zhu; Jingyang Zhao; Jugao Fang (Journal of Photochemistry and Photobiology B: Biology, 2024)

Impact of iron and sulfur cycling on the bioavailability of cadmium and arsenic in co-contaminated paddy soil - Yuepeng Yin; Yurong Wang; Changfeng Ding; Zhigao Zhou; Xin Tang; Liqin He; Ziyao Li; Taolin Zhang; Xingxiang Wang (Journal of Hazardous Materials, 2024)

Differential response of Hg-methylating and MeHg-demethylating microbiomes to dissolved organic matter components in eutrophic lake water - Zhengyu Wu; Zhike Li; Bo Shao; Ji Chen; Xiaomei Cui; Xiaoyu Cui; Xianhua Liu; Ying Xin Zhao; Qiang Pu; Jiang Liu; Wei He; Yiwen Liu; et al. (Journal of Hazardous Materials, 2024)

Boosting selective hydrogenation of α,β-unsaturated aldehydes through constructing independent Pt and Fe active sites on support - Yu Liang; Jieting He; Yurong An; Jiaxing Zhang; Gyeong-Su Park; Liang Zhao; Rena Oh; Xiaoyang Huang; Jinxiang Dong; Lei Liu (Chemical Engineering Journal, 2024)

A novel electrochemiluminescent cytosensor using 3D multivalent aptamer recognition and covalent organic frameworks-associated DNA walker for highly efficient capture and detection of rare CTCs - Minghui Guo; Bo Shen; Wen He; Xinyu Li; Xinmin Li; Menghan Li; Ruiwei Hu; Mengxuan Zhang; Yurong Yan (Chemical Engineering Journal, 2024)

Seawater-based methane storage via mixed CH4/1,3-dioxane hydrates: Insights from experimental and molecular dynamic simulations - Yongji Wu; Ye Zhang; Gaurav Bhattacharjee; Yurong He; Ming Zhai; Praveen Linga (Chemical Engineering Journal, 2024)

Infection with ‘ Candidatus Liberibacter asiaticus’ improves the fecundity of Diaphorina citri aiding its proliferation: A win‐win strategy - Xiaoge Nian; Yaru Luo; Xinyu He; Shujie Wu; Jiayun Li; Desen Wang; Paul Holford; George Andrew Charles Beattie; Yijing Cen; Songdou Zhang; Yurong He (Molecular Ecology, 2024)
The evolution of insect vector‐pathogen relationships has long been of interest in the field of molecular ecology. One system of special relevance, due to its economic impacts, is that between Diaphorina citri and ‘ Candidatus Liberibacter asiaticus’ ( C Las), the cause of the severe Asian form of huanglongbing. C Las‐positive D. citri are more fecund than their C Las‐negative counterparts, boosting opportunities for pathogens to acquire new vector hosts. The molecular mechanism behind this life‐history shift remains unclear. Here, we found that C Las promoted ovarian development and increased the expression of the vitellogenin receptor ( DcVgR ) in ovaries. DcVgR RNAi significantly decreased fecundity and C Las titer in ovaries, extended the preoviposition period, shortened the oviposition period and blocked ovarian development. Given their importance in gene regulation, we explored the role of miRNAs in shaping these phenotypes and their molecular triggers. Our results showed that one miRNA, miR‐275, suppressed DcVgR expression by binding to its 3' UTR. Overexpression of miR‐275 knocked down DcVgR expression and C Las titer in ovaries, causing reproductive defects that mimicked DcVgR knockdown phenotypes. We focused, further, on roles of the Juvenile Hormone (JH) pathway in shaping the observed fecundity phenotype, given its known impacts on ovarian development. After C Las infection, this pathway was upregulated, thereby increasing DcVgR expression. From these combined results, we conclude that C Las hijacks the JH signalling pathway and miR‐275, thereby targeting DcVgR to increase D. citri fecundity. These changes simultaneously increase C Las replication, suggesting a pathogen‐vector host mutualism, or a seemingly helpful, but cryptically costly life‐history manipulation.

Deciphering microbiomes dozens of meters under our feet and their edaphoclimatic and spatial drivers - Haoran He; Jingxiong Zhou; Yunqiang Wang; Shuo Jiao; Xun Qian; Yurong Liu; Ji Liu; Ji Chen; Manuel Delgado‐Baquerizo; Albert C. Brangarí; Li Chen; Yongxing Cui; et al. (Global Change Biology, 2024)
Microbes inhabiting deep soil layers are known to be different from their counterpart in topsoil yet remain under investigation in terms of their structure, function, and how their diversity is shaped. The microbiome of deep soils (>1 m) is expected to be relatively stable and highly independent from climatic conditions. Much less is known, however, on how these microbial communities vary along climate gradients. Here, we used amplicon sequencing to investigate bacteria, archaea, and fungi along fifteen 18‐m depth profiles at 20–50‐cm intervals across contrasting aridity conditions in semi‐arid forest ecosystems of China's Loess Plateau. Our results showed that bacterial and fungal α diversity and bacterial and archaeal community similarity declined dramatically in topsoil and remained relatively stable in deep soil. Nevertheless, deep soil microbiome still showed the functional potential of N cycling, plant‐derived organic matter degradation, resource exchange, and water coordination. The deep soil microbiome had closer taxa–taxa and bacteria–fungi associations and more influence of dispersal limitation than topsoil microbiome. Geographic distance was more influential in deep soil bacteria and archaea than in topsoil. We further showed that aridity was negatively correlated with deep‐soil archaeal and fungal richness, archaeal community similarity, relative abundance of plant saprotroph, and bacteria–fungi associations, but increased the relative abundance of aerobic ammonia oxidation, manganese oxidation, and arbuscular mycorrhizal in the deep soils. Root depth, complexity, soil volumetric moisture, and clay play bridging roles in the indirect effects of aridity on microbes in deep soils. Our work indicates that, even microbial communities and nutrient cycling in deep soil are susceptible to changes in water availability, with consequences for understanding the sustainability of dryland ecosystems and the whole‐soil in response to aridification. Moreover, we propose that neglecting soil depth may underestimate the role of soil moisture in dryland ecosystems under future climate scenarios.

Prediction of the non-uniform drying of wet grain in a fluidised-bed based on a modified CFD-DEM drying model - Hanru Liu; Yurong He; Tianqi Tang; Ming Zhai (Biosystems Engineering, 2023)

Particle coating growth behaviors in a spray fluidized bed based on Gas-Liquid-Solid Quasi-Three-phase DEM numerical simulation - Aiming Deng; Tianqi Tang; Shanshan Sun; Yurong He (Chemical Engineering Journal, 2023)

Fast and efficient methane storage in massive fibrous hydrates produced via pre-frozen activated carbon - Yongji Wu; Yurong He; Ming Zhai; Tianqi Tang (Chemical Engineering Journal, 2023)

Feeding behavior of the notorious invasive Mealybug, Phenacoccus solenopsis to exotic weeds using EPG - Qianjin Wang; Guojun Qi; Yurong He; Lihua Lyu (Journal of Asia-Pacific Entomology, 2023)

Adenosine triphosphate induced transition-metal phosphide nanostructures encapsulated with N, P-codoped carbon toward electrochemical water splitting - Peng Wei; Xueping Sun; Zhimin He; Fangyuan Cheng; Jia Xu; Qing Li; Yurong Ren; Jianhua He; Jiantao Han; Yunhui Huang (Fuel, 2023)

Electroactive bacteria as whole-cell biosensor for sensitive detection of hydrogen peroxide - Junlin Wen; Daigui He; Tongye Zhuo; Wanqing Li; Jianbo Liu; Jialin Wu; Yurong Zhao; Yong Yuan (Journal of Environmental Chemical Engineering, 2023)

Accumulation, transportation, and distribution of tetracycline and cadmium in rice - Chunfeng He; Jini Zhou; Chen Yang; Zhiyi Song; Junheng He; Ziqing Huang; Yurong Deng; Jinling Wang; Yu Xiong; Zhi Dang (Journal of Environmental Sciences, 2023)

A clouded bubble-based mass transfer model for the simulation of gas–solid bubbling fluidization - Kai Zhang; Shuai Wang; Hanyu Jin; Yurong He (Chemical Engineering Journal, 2023)

Environmental regulation and tourism industry development: evidence from China - Genjin Sun; Yanxiu Liu; Qi Qian; Yue He; Yi Shi; Yurong Zhu (Environmental Science and Pollution Research, 2023)

Time dependent correlation of permeability of fly ash concrete under natural tidal environment - Junzhi Zhang; Tao Jin; Yucheng He; Weilong Yu; Yanhong Gao; Yurong Zhang (European Journal of Environmental and Civil Engineering, 2022)

Bacillus megaterium strain WW1211 promotes plant growth and lateral root initiation via regulation of auxin biosynthesis and redistribution - Shengwang Wang; Xiaofan Na; Lei Yang; Cuifang Liang; Li He; Jie Jin; Ziyu Liu; Juan Qin; Junjie Li; Xiaomin Wang; Yurong Bi (Plant and Soil, 2021)

Susceptibility of oriental fruit fly, Bactrocera dorsalis (Diptera: Tephritidae) pupae to entomopathogenic fungi - Desen Wang; Qiling Liang; Minzhong Chen; Hui Ye; Yonglin Liao; Junyi Yin; Lihua Lü; Yanyuan Lei; Dongzhang Cai; Waqar Jaleel; Yurong He (Applied Entomology and Zoology, 2021)

Preparation and identification of an anti-idiotypic antibody antagonist (FG8) for EGFR that shows potential activity against liver cancer cells - Yurong Wang; Fangping He; Helin Zhang; Ying Cao; Yaqing Zhang; Yun Ling; Aliya Rehati (Biotechnology Letters, 2021)

Endoplasmic Reticulum Stress Regulates Cardiomyocyte Apoptosis in Myocardial Fibrosis Development via PERK-Mediated Autophagy - Changjiang Zhang; Yuanhong Li; Jingbo Zhao; Ke Su; Ke He; Yurong Da; Hao Xia (Cardiovascular Toxicology, 2020)

GaHD1, a candidate gene for the Gossypium arboreum SMA-4 mutant, promotes trichome and fiber initiation by cellular H2O2 and Ca2+ signals - Mingquan Ding; Yuefen Cao; Shae He; Jian Sun; Huaqin Dai; Hua Zhang; Chendong Sun; Yurong Jiang; Andrew H. Paterson; Junkang Rong (Plant Molecular Biology, 2020)

Social capital and the use of organic fertilizer: an empirical analysis of Hubei Province in China - Yurong Yang; Yucheng He; Zhaoliang Li (Environmental Science and Pollution Research, 2020)

Nitric oxide and hydrogen peroxide increase glucose-6-phosphate dehydrogenase activities and expression upon drought stress in soybean roots - Xiaomin Wang; Mengjiao Ruan; Qi Wan; Wenliang He; Lei Yang; Xinyuan Liu; Li He; Lili Yan; Yurong Bi (Plant Cell Reports, 2020)

Interactions Between Different Selenium Compounds and Essential Trace Elements Involved in the Antioxidant System of Laying Hens - Xue Lin; Ting Yang; Hua Li; Yinli Ji; Yurong Zhao; Jianhua He (Biological Trace Element Research, 2020)

The reproductive behavior and evaluation of sex pheromone gland extracts of Ectropis grisescens (Lepidoptera: Geometridae) - Tao Ma; Chengqi Zhu; Yurong He; Qiang Xiao; Xiujun Wen (Journal of Plant Diseases and Protection, 2019)

An experimental study on metal precipitation driven by fluid mixing: implications for genesis of carbonate-hosted lead–zinc ore deposits - Yan Zhang; Runsheng Han; Xing Ding; Junjie He; Yurong Wang (Acta Geochimica, 2019)

Alternative respiration pathway is involved in the response of highland barley to salt stress - Qiang He; Xiaomin Wang; Li He; Lei Yang; Shengwang Wang; Yurong Bi (Plant Cell Reports, 2019)

Biology, taxonomy, and IPM strategies of Bactrocera tau Walker and complex species (Diptera; Tephritidae) in Asia: a comprehensive review - Waqar Jaleel; Lihua Lu; Yurong He (Environmental Science and Pollution Research, 2018)

Effects of insecticides on sex pheromone communication and mating behavior in Trichogramma chilonis - Desen Wang; Lihua Lü; Yurong He (Journal of Pest Science, 2018)

Production, identification, and field evaluation of sex pheromone from calling females in Diaphania angustalis (Lepidoptera: Crambidae) - Tao Ma; Zhitao Liu; Cai Wang; Shengnan Zhang; Xianhui Shi; Zhaohui Sun; Xiaoyang Chen; Caijuan Jia; Changlu Wang; Yurong He; Xiujun Wen (Environmental Science and Pollution Research, 2017)

Genetic fine mapping and candidate gene analysis of the Gossypium hirsutum Ligon lintless-1 (Li1) mutant on chromosome 22(D) - Yurong Jiang; Mingquan Ding; Yuefen Cao; Fen Yang; Hua Zhang; Shae He; Huaqin Dai; Huanfeng Hao; Junkang Rong (Molecular Genetics and Genomics, 2015)

Brassinosteroid is required for sugar promotion of hypocotyl elongation in Arabidopsis in darkness - Yongqiang Zhang; Zhongjuan Liu; Jianfeng Wang; Yadi Chen; Yurong Bi; Junxian He (Planta, 2015)

Molecular characterization of a transcriptionally active Ty1/copia-like retrotransposon in Gossypium - Yuefen Cao; Yurong Jiang; Mingquan Ding; Shae He; Hua Zhang; Lifeng Lin; Junkang Rong (Plant Cell Reports, 2015)

Intraspecific mass scaling of metabolic rates in grass carp (Ctenopharyngodon idellus) - Yurong Zhang; Qingda Huang; Shuting Liu; Dingcong He; Gang Wei; Yiping Luo (Journal of Comparative Physiology B, 2014)

Hydrogen peroxide is involved in the regulation of rice (Oryza sativa L.) tolerance to salt stress - Xiaomin Wang; Chen Hou; Jie Liu; Wenliang He; Wenbin Nan; Huiling Gong; Yurong Bi (Acta Physiologiae Plantarum, 2013)

Real-time quantitative analysis of the influence of blue light on citrinin biosynthetic gene cluster expression in Monascus - Changlu Wang; Hua Yang; Mianhua Chen; Yurong Wang; Fengjuan Li; Cheng Luo; Shuyi Zhao; Dong He (Biotechnology Letters, 2012)

Synthesis of 2-R1-2-(4-(2-fluoroethoxy)benzamido)acetate as potential PET imaging agents - Yong He; Jingli Xu; Hang Liu; Man Feng; Xiao Wang; Rui Ding; Chuanmin Qi; Yurong Chen; Fang Li; Zhao-Hui Zhu; Yong-Hong Dang; Ming Wang; et al. (Medicinal Chemistry Research, 2012)

Complete sequence of a viral nervous necrosis virus (NNV) isolated from red-spotted grouper (Epinephelus akaara) in China - Hong Liu; Yong Teng; Xiaocong Zheng; Yurong Wu; Xiayang Xie; Junqiang He; Yiyou Ye; Zhixin Wu (Archives of Virology, 2012)

Micromorphological features of diagnostic horizons in several soils in southwest China: Implication for soil taxonomic classification - Xiangming Xu; Yurong He; Chengmin Huang; Donghong Xiong (Journal of Mountain Science, 2010)

Micromorphological features of Paleo-Stagnic-Anthrosols at archaeological site of Sanxingdui, China - Yurong He; Chengmin Huang; Xiangming Xu; Yanqiang Wang; Xiubin He (Journal of Mountain Science, 2008)

Zonal distribution of the erosion-landslide and soil micromorphological features in purple hilly region - Yurong He; Chaolin Liao; Pei Xu; Baohua Zhang (Journal of Mountain Science, 2005)